Efektifitas Incenerator Untuk Pembakaran Sampah Medis di RSUD Kota ABC - Hasti Suprihatin (Universitas Riau, 2018)
To reduce the number of germic or nosocomial infections, especially come from waste disposal. Especially for hospitals, the disposal procedure should cut off the chain of transmission or the spread of disease which are came from the clinical waste or medical waste by burning the clinical waste or medical waste using the incinerator. Incenerator is used with high temperature by 800 ° C. Incenerator has been proven to reduce medical waste about 70% to 90%, but it can also reduce the number of pathogenic bacteria to zero in percentage. In the using of incinerators, there has not been an assessment of the effectiveness of incinerator usage until today. Research method which has been used is analytical research to determine the effectiveness of incinerator usage due to the destruction of the medical waste. The result of examination about effectivity of incinerator usage for 4 times of combustion was obtained that the burning volume of medical waste exceeding the required incenerator volume of 0.7 m3/day is very ineffective with the burning time for 2 hours, because of the results of the research with different volume shows that the volume of 0.7 m3 is an effective volume for incinerators in Public Hospital of ABC City, this is being streghtened based on the results of hypothesis testing that shows the volume of 0.7 m3 would be more effective volume and could give a significant result. In fact, the medical waste should be burnt twice a day in order to be able to burn all the medical waste which is generated.